FACTORS INFLUENCING THE FORMATION OF TABOOS AND EUPHEMISMS IN ENGLISH AND UZBEK CULTURES - D.B.Olimova (Western European Studies, 2025)
This paper explores the socio-cultural and linguistic factors that influence the formation of taboos and euphemisms in English and Uzbek cultures. By comparing the fundamental values, religious beliefs, historical backgrounds, and communicative norms of the two linguistic societies, the study highlights similarities and differences in their approach to delicate topics. The results suggest that while general human concerns contribute to common taboo domains, cultural specificity deeply affects how these taboos are mitigated through euphemisms
Keywords: taboo; euphemism; culture